Diastereoselective intramolecular hydride transfer under brønsted acid catalysis - Wang, Bin (2020)
A diastereoselective hydride transfer process has been developed under Brønsted acid-catalyzed reaction conditions using methyl ethers or acetals as hydride donors and tertiary alcohols or alkenes as precursors of carbocation. The method enables construction of complex molecules having multiple stereogenic centers from rather simple and readily available starting materials with predictable diastereoselective control.